Digital Banking Adoption in Indonesia: The Role of Perceived Usefulness and Ease of Use - Andhi Febisatria; Zulfahmi; Eureka Try Zarazwanty R. Laega; Leonardo Davidsi Sipayung Davidsi Sipayung; Aryan Agus Pratama (Target : Jurnal Manajemen Bisnis, 2025)
The advancement of digital technology has revolutionized the banking industry, enabling greater convenience, speed, and efficiency in financial transactions. This study aims to analyze the influence of perceived usefulness and perceived ease of use on behavioral intention to use the Livin’ by Mandiri appli- cation, employing the Technology Acceptance Model (TAM) as the theoretical framework. A quantitative research approach was used through a survey of 100 active Bank Mandiri customers who have used the Livin’ by Mandiri application for at least 1 year. Purposive sampling was used to select respondents, and data were analyzed using multiple linear regression in IBM SPSS Statistics 22. The findings indicate that perceived usefulness and perceived ease of use both have a positive and significant impact on behavioral intention to use. These results confirm that user perceptions of benefits and ease of use are key drivers of digital banking adoption. Accordingly, this study reinforces the relevance of the TAM model in explaining the adoption behavior of digital banking technologies among urban communities in Indonesia, which are increasingly adaptive to digital transformation in the financial sector.